Circulation of influenza B lineages in northern Viet Nam, 2007–2014 - Le, Thanh Thi; Pham, Hang Thu; Pham, Hien Thi; Nguyen, Hang Khanh Le; Nguyen, Thach Co; Hoang, Phuong Mai Vu; Tran, Huong Thu; Nguyen, Son Vu; Ngo, Giang Huong; Le, Mai Quynh (Western Pacific Surveillance and Response, 2015)
Introduction: Influenza B viruses circulate throughout Viet Nam, and their activities vary by region. There have been two antigenically distinct lineages of influenza B viruses co-circulating in the past 20 years; however, only one lineage is selected as a component of contemporary trivalent seasonal influenza vaccines. To improve the understanding of circulating influenza B lineages and influenza vaccine mismatches, we report the virus lineages circulating in northern Viet Nam over an eight-year period (2007–2014). Methods: Lineages of 331 influenza B viruses were characterized by haemagglutination inhibition assay against standard reference ferret (Yamagata) and sheep (Victoria) antisera. Sequence analysis of the haemagglutinin gene was performed in 64 selected influenza B isolates. Results: The proportion of influenza B lineages changed by year. The Yamagata lineage predominated in 2007, 2008 and 2012; the Victoria lineage predominated in 2009–2014 except 2012. The two lineages showed continuous evolution over time. The Northern Hemisphere’s influenza vaccine components were mismatched with the predominant circulating viruses in 2007, 2009 and 2014. Discussion: The seasonality of influenza B activity is more variable in tropical and subtropical regions than in temperate zones. Our data showed a common co-circulation of both influenza B lineages in northern Viet Nam, and it was difficult to predict which one was the predominant lineage. Quadrivalent influenza vaccines containing both lineages may improve the effectiveness of influenza vaccine programmes in the future.